Low‐Threshold Bound State in the Continuum Lasers in Hybrid Lattice Resonance Metasurfaces. Issue 10 (16th August 2021) - Yang, Jhen‐Hong; Huang, Zhen‐Ting; Maksimov, Dmitrii N.; Pankin, Pavel S.; Timofeev, Ivan V.; Hong, Kuo‐Bing; Li, Heng; Chen, Jia‐Wei; Hsu, Chu‐Yuan; Liu, Yi‐Yun; Lu, Tien‐Chang; Lin, Tzy‐Rong; et al.
Abstract: Bound states in the continuum (BICs) have attracted considerable research attention due to their infinite quality factor ( Q ‐factor) and extremely localized fields, which drastically enhances light–matter interactions and yields high potential in topological photonics and quantum optics. In this study, the room temperature directional lasing normal to a BIC metasurface is demonstrated with hybrid surface lattice resonances. Compared to the plasmonic nanolasers, the BIC metasurface lasers possess directional radiation and a larger emission volume. The high Q ‐factor resonance of BIC metasurface overcomes the limitation of a large mode volume in achieving low‐threshold lasing. In addition, a design rule is proposed to prevent the occurrence of wavelength shift when the Q ‐factor changes; thus, the lasing thresholds for different BIC metasurfaces can be compared. In this work, the high localization ability of BICs is used to achieve the low lasing threshold (1.25 nJ) at the room temperature. The "light in–light out" diagram of the aforementioned laser based on simulations and experiments exhibits a large spontaneous emission coupling factor ( β = 0.9) and the S‐curve. The device developed in this study can be used in various applications, such as quantum emitters, optical sensing, nonlinear optics, and topological states engineering. Abstract : Bound states in the continuum (BICs) laser, which possess directional radiation and large emission volume, is demonstrated by using dielectric metasurfaces with hybrid surface lattice resonance. The high Q ‐factor resonance of the BIC metasurface overcomes the limitation of a large mode volume in achieving low‐threshold lasing. Moreover, photoluminescence and reflection reveal the mechanism behind the BICs with internal and external excitation.